CHARACTERISTICS OF PARONYMS IN THE UZBEK LANGUAGE - Yusupova Soxiba Islombek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article examines the linguistic characteristics of paronyms in the Uzbek language, focusing on their phonetic similarity and semantic distinctions. The study analyzes the formation, classification, and functional features of paronyms, as well as their role in oral and written communication. Particular attention is paid to the causes of confusion between paronyms and the types of lexical and stylistic errors that arise from their incorrect usage. Through descriptive and comparative analysis, examples of paronymic word pairs are explored to illustrate their usage in different communicative contexts. The findings of the study contribute to a clearer understanding of paronymy in Uzbek linguistics and highlight its importance in improving speech culture and language competence.